Seed Quality Comparison of Mung Bean Lines - PIYADETH, S; KHOUNGVICHITH, P; PHOUTTHAVONGSA, T; INTHAVONGSA, T (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Seed quality Comparison of new mung bean lineswas tested. The 8x3 split plot was conducted in completely randomized design with 3 replications in the main plot consisted of 8 mung bean lines: line SM1, SM4 SM5, SM6 and SM7 in comparison with three standard varieties KPS1 KPS2 and CH72. The sub plot was 3 seasons, 1) in the late of rainy season 2) Rainy season and 3) Dry season during 2018-2019. Seed quality testing was performed followed by the procedure of International Seed Testing Association 2013 at Maejo University. The objective of this research was to test the seed quality of new mung bean lines in a period of 3 seasons. The results revealed thatpurity, moisture content, percent of germination, seed vigor and normal seedling weight of mung bean line #1 and #7 was non-significance differently compared to the 3 standard varieties, seed purity were 98.48 and 98.10%, moisture contentwere 11.20 and 10.98%, percent of germination were 84.22 and 88.89%, seed vigor were 87.56 and 78.89% and weight of normal seedling were 48.06 and 44.21 mg/seedling respectively. Mungbean line SM1 and SM7 was able to adapt to each seasons as the same with standard varieties. Mungbean line SM1 and SM7 could be improved and developed as a new variety to support for the farmer in future.